Использование мобильного обучения как современной информационной технологии в изучении иностранного языка в учреждениях образования - Kenzhegulov, B. Z.; Bagitova, K. B.; Rakhymbergenova, A. G. (Journal of Educational Sciences, 2017)
The article examines the directions of mobile learning in modern education. It is noted that despite the widespread availability of mobile phones among students, mobile learning poorly distributed in high schools. The technical and psychological readiness of students to use of mobile technology in learning is analyzed. It concludes_ that most of today’s students are ready both technically and psychologically to use mobile technology in education, and it is necessary to consider new opportunities for more effective use of mobile learning. Key words: mobile learning, methods of mobile learning, student’s readiness to mobile learning.